Proposed an upgrading of Sri Balang Restaurant at Lot 10,12&14,Jalan 4/12A,Seksyen 4 Tambahan 43650,Bandar Baru Bangi,Selangor Darul Ehsan / Nurliyana Raud'zah Nila Utama - Nila Utama, Nurliyana Raud'zah (Faculty of Architecture, Planning and Surveying, 2012)
Sri Balang Restaurant at Lot 10,12 & 14,Jalan 4/12a,Seksyen 4 Tambahan,43650,Bandar Baru Bangi,Selangor darul Ehsan for Anggun Kenali Enterprise is the product for this final project.The purposed of this project is to upgrade the existing site to a highly competative environment so they can compete with other restaurant around the area. To rearrange the space and provide a better space requirement for the restaurant.Trying to attract identified markets of customers and comunicate a more suitable image for Sri Balang Restaurant because Sri Balang dont even have their own image and concept.Create a comprihensive style and quality of embience appropriate to customers expectations.The design reflect the basic concept,including range of menu and food preparation involved because Sri Balang restaurant serve many type of menu originally from Kelantan cuisine. In conclusion,Sri Balang Restaurant need a new image and concept that suits their menu.They should have the characteristic to fullfill their client needs.The requirement evolve with a desire to change,new style of trend and wider experience of meals.